THE INFLUENCE OF PRICE PERCEPTION, CUSTOMER TRUST, AND CUSTOMER EXPERIENCE ON PURCHASING DECISIONS AT MTM PHARMACY IN BEKASI - Setiawan, Lukas; Keni , Keni (International Journal of Application on Economics and Business, 2023)
Pharmacy is one of the healthcare facilities supported by the Pharmaceutical Industry as the final means to directly sell to the public. This research aims to determine the influence of price perception, customer trust, and customer experience on purchasing decisions of MTM Pharmacy products/services in Bekasi. The subjects of this study are MTM Pharmacy customers, with a total sample size of 80 respondents. The sample selection was done using non-probability sampling with purposive sampling technique. The method used is Partial Least Square – Structural Equation Modeling (PLS-SEM). The results show that all four variables are declared valid with AVE values greater than 0.5, and the reliability test with Cronbach's Alpha parameter for all four variables shows values greater than 0.6. Furthermore, the results of the direct influence test of the three independent variables show that price perception has a (positive) influence on purchasing decisions with p-values of 0.000; customer trust has a (positive) influence on purchasing decisions with p-values of 0.016; and customer experience has a (positive) influence on purchasing decisions with p-values of 0.001."